'We want to, but we can't': pre-service teachers' experiences of learning to teach primary physical education. (4th March 2023) - Randall, Vicky
ABSTRACT: A growing trend in primary schools in recent times has been to outsource Physical Education (PE) to external sport and activity providers. The impact of this has not yet been examined on new teachers entering the profession. Drawing upon Critical Theory, this paper aims to explore and understand pre-service teachers' (PSTs) school-based experience of learning and teaching in primary PE. A total of 625 PSTs took part in the study, representing a variety of routes into primary teaching. Quantitative data were obtained, identifying the number of lessons taught by PSTs, and their perceived confidence and willingness to teach. Qualitative data were also gathered to examine the contextual factors influencing PSTs' development. Findings showed that while PSTs were both willing and confident to teach primary PE, over a third were unable to do so. Reasons were predominantly attributed to curriculum outsourcing and perceived low subject priority in initial teacher education.